Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005495.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental intervention programs post hospital discharge to prevent motor and cognitive impairments in preterm infants

Abstract: Early developmental intervention programs post hospital discharge to prevent motor and cognitive impairments in preterm infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
2
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(161 citation statements)
references
References 80 publications
2
144
2
13
Order By: Relevance
“…21,24 A recent review assessed post-discharge early developmental intervention for preterm infants. 25 However, this review did not focus on interventions involving parents. This review aims to determine whether early interventions aimed at either teaching parenting skills, and/or involving parents in the hospital care of the preterm, improve either short-term and school-age neurodevelopmental outcomes of premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…21,24 A recent review assessed post-discharge early developmental intervention for preterm infants. 25 However, this review did not focus on interventions involving parents. This review aims to determine whether early interventions aimed at either teaching parenting skills, and/or involving parents in the hospital care of the preterm, improve either short-term and school-age neurodevelopmental outcomes of premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from developed countries indicate that early intervention is critical to improved motor and cognitive impairments and such interventions are currently unavailable in Zambia. 29 All infants who presented for follow-up were included in the analyses; however, the characteristics of the infants who failed to keep the appointment are not known. Although previous studies in developed countries have found a bias in the outcomes of infants who present for long-term follow-up, [30][31][32] it is unclear if this is true in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…From the systematic review by Spittle et al, 9 randomized controlled trials were selected that were preventive and family centred in nature -with at least part of the intervention programme in the home after discharge from the NICU -which were carried out in non-selected groups of very preterm infants and aimed to at least improve cognitive development at age two. By subsequently searching related papers to the selected trials in PubMed, later publications of the same trial were found as well as one additional randomized trial.…”
Section: Methodsmentioning
confidence: 99%